Oviposition and olfactometry response of codling moth (Cydia pomonella) to quince (Cydonia oblonga) cultivars - Gomez, María Pía; Jofré Barud, Flavia; Díaz, Ariel; Lopez, María Liza (Wiley, 2023)
Quince (Cydonia oblonga Miller) is one of the common hosts of the codling moth, Cydia pomonella L. Knowledge of the chemical ecology of codling moth is based on its behaviour against apples and pears but not quince. Here, we present a laboratory study on olfactometry and oviposition behavior preference of mated females and neonate larvae of codling moth against four quince cultivars. Oviposition of mated females was evaluated on dual-choice test, whereas olfactometry response was evaluated in a Y-tube olfactometer. Neonate larvae were evaluated in a dual-choice test between pieces of fruit of quince cultivars in pairwise comparisons. In the Y-tube olfactometer assay, mated females always responded positively to the fruit-scented arm to quince fruit volatiles. Smyrna and Champion cultivars showed significant differences in the time that mated females spent in the fruit-scented arm. In the oviposition assay, all pairwise comparisons showed significant differences in the number of the eggs laid, with Smyrna and Champion being the cultivars most preferred. No significant differences were detected in dual choice of neonate larvae. All comparisons elicited the behaviour of contacting the fruit source. Based on the potential emission of recognized kairomones and the results found here, cultivars Smyrna and Champion are suggested as cultivars most susceptible to codling moth infestation.